Letting Go (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
My mom didn’t allow me to hold anything close. Not her or my dad. She bathed me in discomfort. Dried me in shame. Let me feel the uttermost of temperatures. I had to find footholds. Learn that branches break. I slipped, fell in mud. Stood up without help. Today I held her memory close without fear to let her go. My mom taught me what freedom is.